Forecasting water discharges on the mountain river Arpa (Armenia) - Gaidukova Ekaterina; Margarian Varduhi; Mirzoev Vagif; Batmazova Anna; Vinokurov Igor (E3S Web of Conferences)
The work is aimed at testing mathematical models in the form of differential equations for short-term forecasting of water content of a small mountain river in Armenia. The hydrometeorological characteristics of the Arpa River, Jermuk post were used as initial data: water discharges, precipitation amount, air temperature, snow depth in the catchment area. Verification forecasts of water discharges from March to July for nine years were issued with a daily lead time. It was found that for the Arpa River, the first and second order models show satisfactory results in forecasting water discharges during the spring flood. The best results are shown by the second order model, which takes into account both surface and subsurface runoff. It was revealed that the model parameters can be optimized with a large error, in particular, the coefficient responsible for the intensity of snowmelt. An analysis of the obtained results was made, which were transferred to the Hydrometeorological Center of Armenia.